Synergy Between Smallholder Palm Oil Replanting Policies and Green Energy Initiatives: A Study of Impacts and Policies in Indonesia - Mayarni Mayarni; Heriyanto Meyzi; Nasution Mimin Sundari; Arumbinang Mohammad Hazyar (E3S Web of Conferences)
People’s Palm Oil Replanting (PSR) and green energy projects are crucial Indonesian initiatives aimed at achieving economic and environmental sustainability. This study explores the synergies between these programs, analyzing their impacts and interactions within natural resource management and sustainable energy. Using a qualitative case study approach, data were collected through stakeholder interviews, policy document analyses, and field surveys across five major palm oil-producing districts in Indonesia. The findings show that integrating PSR and green energy initiatives can enhance land productivity, reduce carbon emissions, and improve peatland management. PSR projects, focused on rejuvenating aging oil palm plantations and adopting environmentally friendly technologies, support more efficient bioenergy production. Simultaneously, green energy initiatives promote renewable energy use and incentivize sustainable practices. However, challenges such as limited collaboration, budget constraints, and farmer resistance persist. To address these, this study proposes a policy framework including financial support, technical training for farmers, and improved stakeholder communication. By examining the intersection of agricultural and energy policies, this research highlights strategies to achieve sustainability goals and provides actionable insights for policymakers to design integrated, effective approaches that maximize the benefits of these initiatives